The Relationship between Workload and Nursing Job Satisfaction in One Private Hospital in The West Region of Indonesia - Dora Irene Purimahua; Gita Martinaningtyas; Lenceria Girsang; Widia Astuti; Martina Pakpahan (Fakultas Keperawatan Universitas Andalas, 2020)
Nurse as a profession and caregiver who composed the large portion of healthcare service workers is required to have high expertise in carrying out nursing practice, the speed at work, and high work volume. With these important roles, the income earned by nurses is still in the low category as a healthcare provider that makes nurses feel dissatisfied in their work. The purpose of this study was to describe the workload of nurses, level of work satisfaction and to find out the relationship between the workloads in nursing and the job satisfaction in one private hospital in the west region of Indonesia. This study used a quantitative method with a cross-sectional approach. Data were collected using a questionnaire of nursing workload and nursing job satisfaction on 126 nurses in one private hospital in the west region of Indonesia with a total sampling technique. Univariate and bivariate were conducted to analyze the collected data. This study found that there were 55% of nurses with high workload and 52% of nurses with job dissatisfaction. There was a relationship between workloads to nursing job satisfaction (p-value 0.001). This research recommend the hospitals to re-evaluate nurses job satisfaction, give reward and set excellent and evident career path in nursing.